How to Support Employment for the Elderly People through the Intergenerational Self-Help Model. The Story from Vietnam - Nguyen Nam Phuong; Vu Thi Uyen (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
Vietnam is in the process of population aging, and there is still a large proportion of the elderly people living in rural areas who continue to work for extra income either for themselves or to support their descendants. However, the elderly people have problems with their health and suitable requirements for finding suitable jobs. The question in this paper is that: how to help the elderly people find suitable jobs. To answer it, this paper did both qualitative and quantitative analyses. Descriptive statistics are used to describe the relationship between factors and employment supports for the elderly people, while a multivariate regression is used to find the determinants of effective employment supports. In addition to secondary data collected from various sources, primary data was obtained from in-depth interviews with some local officials and elderly people in the suburbs of Hanoi to assess related issues in management and implementation of policies. The findings show that the Intergenerational Self-Help Club (ISHC) model has contributed positively to improving the lives of the poor and near poor elderly people by helping them to get jobs through employment supporting activities in many aspects such as trainings in techniques of cultivation, husbandry and production; provision of loans, seeds, fertilizers, and other required inputs for production; and provision of information on suitable jobs that not only to improve their incomes significantly, but also suitable to their health conditions. The model not only contributes to raising living standards but also helps the elderly people to live happily and healthily through diverse activities. This effective and low cost model is well suited to urban, rural, coastal and ethnic minority and mountainous areas. Based on this fact, this paper proposes some solutions to replicate the model for increasing production capital, strengthening trainings of production techniques for the elderly people, diversifying the areas of help in the employment support in the model, mobilizing resources from the community, and mobilizing stakeholder participations to help them have decent jobs.